Anti-export bias in the export-oriented economy of Sri Lanka - Abeyratne, S. (My University, 1992)
Sri Lanka, which in 1960 had almost the same per capita GNP and the same production structure as some East Asian Newly Indusrialized Countries(NICs), today lags behind them. Why have the economies of East Asian NICs grown so rapidly, while those of Sri Lanka and many other developing countries grew slowly over the last three decades? Why does Sri Lanka's manufacturing value added to GDP ratio remain at the level it was two decades ago?...